Therapeutic deep eutectic solvent with saponin, optimized through response surface methodology, exert potent in vivo antimicrobial effects against Pseudomonas aeruginosa - Ramya M. Subramani; Bhanuvalli R. Shamprasad; Narayana Shri Sanjeev Viswanathan; Saisubramanian Nagarajan; Arvind Sivasubramanian (Scientific Reports)
Abstract Therapeutic deep eutectic solvents (THEDES) are a type of deep eutectics that can be used as active pharmaceutical ingredients (APIs) by enhancing the drug bioavailability, by increasing the solubility of APIs in aqueous solutions or by increasing their permeability through biological barriers. In this study, we demonstrate the utility of designer THEDES, based on Quillaja Saponin (SAP), a triterpene natural product to unravel the antimicrobial potential of such THEDES. THEDES were prepared by gently mixing and heating five different α- hydroxy acids- malic, citric, tartaric, glycolic, lactic acids and SAP with water as a third component in the THEDES. The antimicrobial assays were performed with the as-prepared SAP-THEDES and among the panel of bacterial strains, saponin-malic acid THEDES [SMA-THEDES] displayed potent activity in disassembling PA biofilms, demonstrating that the SMA-THEDES can serve as therapeutic antibacterial biomaterials. To further optimize, a Box-Behnken- response surface methodology (RSM) experimental design was done and at the optimum conditions of SAP (1.014 m.mol), Malic acid (1.003 m.mol), Water (0.117 m.mol), SMA-THEDES exhibited maximum MIC of P. aeruginosa with the minimum absorbance at 590 nm of 0.105. The effectiveness of SMA-THEDES as antibiofilm agents on P. aeruginosa with the mechanism studies have been explored. The colony count from the in vivo infection zebrafish model in the treatment group showed a decline of > 2 fold for SMA-THEDES. Toxicity studies did not reveal any abnormality in liver and brain enzyme levels. Liver morphology images show no severe cytological alterations when treated with SMA-THEDES and were almost similar to the normal liver.